Kajian Scientometric pada Penelitian Meta-Analisis Tema Ayam Broiler (Scientometric Study on Meta-Analysis Research in the Field of Broiler) - Fitra, Deni - (Journal of Tropical Animal Science and Technology, 2024)
Scientometrics is the quantitative study of scientific literature aimed at measuring and analyzing publication patterns, research collaboration, and development trends in specific fields. This research a scientometric method with five work stages: recovery, migration, analysis, visualization, and interpretation. The publication data source is derived from the Scopus database, using the search keywords "meta-analysis and broiler," resulting in 228 publication documents spanning the years 2001-2023. Data analysis and visualization are conducted using R-Studio, Bibliometrix, and VOSviewer. The use of meta-analysis in broiler chicken research began in 2001 and has significantly increased since 2019, with 155 articles or 67.9% of total publications produced in the last five years. The majority of publications are journal articles (157 documents) and review articles (59 documents). Poultry Science journal is the most chosen publication source with 36 publications, H-Index of 18, and 884 citations. Jayanegara A is the author with the highest number of publications from Indonesia, affiliated with IPB University, while the most cited author is Newell DG from the Veterinary Laboratories Agency, Addlestone, United Kingdom, with the article titled "Biosecurity-Based Interventions and Strategies to Reduce Campylobacter spp. on Poultry Farms." Brazil is the country with the highest number of publications, whereas authors with the most collaborations are from the USA. Research trend analysis using keyword analysis shows that themes like animal food, animal feed dietary, salmonella, and veterinary medicine are more popular. The future research landscape, as suggested by the thematic map analysis, recommends researchers to focus on themes such as heat stress, antioxidants, antimicrobial resistance, and food safety.